Material strength consideration in the design optimization of nonlinear energy harvester - Upadrashta, Deepesh (2014)
Cantilever-based piezoelectric energy harvesting from ambient vibrations is a viable solution for powering wireless sensors and low-power electronic devices. For realization of such technology, it is imperative to design the energy harvester with higher power output and wider operating bandwidth. The main practical constraints on the design of harvester are system mass, volume, and strength of the material. In pursuit of better performance, material strength has yet been considered in designing nonlinear energy harvesters in the literature. This article focuses on the design optimization of nonlinear energy harvester with magnetic oscillator within the limits of allowable strain on piezoelectric material. Parametric study is carried out to find the optimal configuration of nonlinear energy harvester. Experiments show that compared to the linear configuration, the optimized nonlinear energy harvester achieves higher power output and wider bandwidth with maximum strain on piezoelectric material below the allowable limit.